On The Essence of the Concept of State and its Modern Interpretation: The Case of New Uzbekistan (Eurasian Research Bulletin, 2022)
The article analyzes the concept of the essence of the state, the views of thinkers on the essence of the state, questions of the essence of the state of New Uzbekistan from a scientific and theoretical point of view.